2020
DOI: 10.3390/cancers12102896
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Cancer-Associated Fibroblasts as an Indispensable Cellular Player in Bone Metastasis Process

Abstract: Bone metastasis is frequently complicated in patients with advanced solid cancers such as breast, prostate and lung cancers, and impairs patients’ quality of life and prognosis. At the first step of bone metastasis, cancer cells adhere to the endothelium in bone marrow and survive in a dormant state by utilizing hematopoietic niches present therein. Once a dormant stage is disturbed, cancer cells grow through the interaction with various bone marrow resident cells, particularly osteoclasts and osteoblasts. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 126 publications
(147 reference statements)
0
26
0
Order By: Relevance
“…In this study, using a 3D microfluidic platform, we modelled the reciprocal interaction between CAFs and breast carcinoma cells. Using our invasion and migration model, we demonstrated that CAFs promote spheroid formation and the migration capacity of carcinoma cells [15], possibly through the secretion of cancer-promoting cytokines that play a haptotactic or chemotactic role for carcinoma cells [52]. Following treatment with PFD, we found that PFD significantly reduced the migration of an invasive type of breast cancer cells and CAFs, and significantly decreased the expression of EMT marker vimentin, stemness marker CD44, and YAP1 in CAF-tumor spheroids at the protein level [41].…”
Section: Discussionmentioning
confidence: 92%
“…In this study, using a 3D microfluidic platform, we modelled the reciprocal interaction between CAFs and breast carcinoma cells. Using our invasion and migration model, we demonstrated that CAFs promote spheroid formation and the migration capacity of carcinoma cells [15], possibly through the secretion of cancer-promoting cytokines that play a haptotactic or chemotactic role for carcinoma cells [52]. Following treatment with PFD, we found that PFD significantly reduced the migration of an invasive type of breast cancer cells and CAFs, and significantly decreased the expression of EMT marker vimentin, stemness marker CD44, and YAP1 in CAF-tumor spheroids at the protein level [41].…”
Section: Discussionmentioning
confidence: 92%
“…One of the important reasons is tumor cell-stromal cell interactions (40). This preferential [ 68 Ga]Ga-DOTA-FAPI-04 accumulation is likely associated with the presence of CAFs in tumor stroma of bone metastases (41).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, macrophages were shown to play an important role in tumor recurrence and metastatic outgrowth in murine models (206,(315)(316)(317)(318)(319). During the metastatic cascade, CAFs and M2 macrophages can collaborate in altering the functions of other stromal cells as well as the tumor cells (250,320). Nielsen et al reported that early recruitment of granulin secreting inflammatory monocytes to the liver is very important for pancreatic ductal adenocarcinoma liver metastasis.…”
Section: The Effects On Tumor Progressionmentioning
confidence: 99%